TINGKAT KEPUASAN SISWA TERHADAP PEMBELAJARAN PJOK SECARA DARING DI MASA COVID-19 TAHUN 2021 - Aser Paul Nainggolan; Rizki Bastanta B Manalu (JURNAL CURERE, 2022)
The purpose of this study is to determine the level of student satisfaction in SMP Cahaya Pengharapan Abadi Class VIII on daring PJOK learning in the Covid-19 Pandemic Era in 2021. This type of research is a quantitative descriptive research using survey methods. In this study, questionnaire instruments were used for data collection, and descriptive statistics with percentages were used for data analysis. The population of this study was 28 students of class VIII SMP Cahaya Pengharapan Abadi. The validity is 0.781 and the reliability is 0.925, indicating that the instrument used in this study is valid and reliable. The results showed that the level of satisfaction of students of class VIII SMP Cahaya Pengharapan Abadi towards learning PJOK daring during the Covid-19 pandemic was in the category of "very satisfied" that is 0 students (0%), the category of "satisfied" as many as 3 students (10.71%) , the category of "enough" 18 students (64.29%), the category of "dissatisfied" 5 students (17.86%) and the category of "very dissatisfied" 2 students (7.14%), so that the satisfaction of student participants in SMP Cahaya Pengharapan Abadi is included in the category of sufficient.